Evolving crop-livestock farming systems in the humid zone of West Africa - Jabbar, M.A. (1993)
Cattle rearing in humid West Africa was nearly impossible in the past owing to the prevalence of trypanosomiasis. However in recent times, with population pressure, jungle clearance, crop cultivation and tsetse control measures, the challenge has been reduced. Consequently there has been an influx of transhumant cattle rearers who used to visit the zone for dry season grazing and return to the safer sub-humid/semiarid zones in the wet season. An increasing number of them have begun to settle in the humid zone and are adopting crop-livestock mixed farming. There is also a tendency among some local crop farmers to adopt livestock gradually in the farming system. Consequently, new farming systems and its implications for systems oriented research by national and international centres are examined.